Implementation of Adventure Education-Based Physical Education Learning on the Kinesthetic Intelligence Class X Students of SMAN 9 Semarang - Tiara Yuliana; Bertika Kusuma Prastiwi; Priyo Hutomo (PHEDHERAL, 2024)
Research on adventure education learning was carried out because this method was considered effective in improving student learning outcomes, both in terms of academic ability and personality development. Apart from that, this method is also believed to be able to improve social relations between students, as well as improve physical and mental health. This type of research uses True Experimental Design research. The sample collection technique is carried out using purposive sampling. The independent variable (X1) in this research is adventure education, while the dependent variable is kinesthetic intelligence (Y). Data collection techniques through observation and tests. Data analysis techniques are descriptive statistical analysis, normality test, homogeneity test, hypothesis test. The results of research related to the influence of adventure education-based physical education learning on kinesthetic intelligence in class X students at SMAN 9 Semarang for the 2024/2025 academic year, namely the adventure education learning model, show that there is a significant influence on kinesthetic intelligence in physical education learning for class X students at SMAN 9 Semarang.